Gendered Bodies that Matter: Crossnature, Belonging and Writing in Nina Bouraoui’s Work - Baazaoui, Zayer (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
In this article, I study Nina Bouraoui’s two auto fictional novels, Garçon manqué (2000) and Mes Mauvaises Pensées (2005). My intended task is to show the merit of Nina Bouraoui in highlighting non-normative female sexuality. Like in the works of several Maghrebian writers of French expression (Ben Jelloun, Assia Djebar, Albert Memmi, etc.) and especially in the case of Nina Bouraoui, due to her dual nationality, there is a critical and deconstructive conversation about the notion of belonging, which will be read in the two novels here at stake. This conversation around citizenship is different from the one that can be found among other writers because it is supported by a discourse on non-normative female sexuality. I consider how belonging to France/Algeria shapes the configuration and appropriation of the space as queer, comparing metropolitan France to postcolonial Algeria. This essay then goes on to discuss the narrator’s negotiation of these two different spaces, examining issues around desire and (dis)comfort. Moreover, in both novels the narrator develops a special relationship with space in general and with nature and its elements in particular. These natural elements are present in an obsessive way, water particularly in the image of the sea. So how does the writer engage with her space? My intent is to critically examine the values, images, and tropes associated with the intersection of non-normative sexuality and nature, as presented in the two novels.